Protagonismo juvenil na Universidade Católica de Santos (1986-1990) : lideranças na Faculdade de Direito. - Vicente, Neusa Lopes (2017)
Historical records show that youth play a significant social role in the world. This free movement, committed and led by young people has aroused the attention of society and is understood as a youth protagonism. The research aimed to understand the contribution of the Catholic University of Santos (UNISANTOS) to the exercise of youth protagonism in its Faculty of Law. The research focused on the period between 1986 (year of creation of the University) and 1990, year of graduation of these first entrants. The object of study were the student leaders elected to the board of the then Academic Directory ""Alexandre de Gusmão"", a student body of the Faculty of Law. The theoretical contribution is in the fields of Sociology of Youth with Machado Pais (2006), in the social theme of the youth in Abramo (1997) and in Social Psychology with Stamato (2008). The methodology focuses on the consultation of documents and institutional records of UNISANTOS and the Academic Directory and the news published in the national and regional press. The testimony of former presidents of the student body and of persons who held positions of academic and administrative management in that period of time corroborate the investigative process.